2022
DOI: 10.1038/s41467-022-29760-0
|View full text |Cite
|
Sign up to set email alerts
|

Honeybee gut Lactobacillus modulates host learning and memory behaviors via regulating tryptophan metabolism

Abstract: Honeybees are highly social insects with a rich behavioral repertoire and are a versatile model for neurobiological research. Their gut microbiota comprises a limited number of host-restricted bacterial phylotypes that are important for honeybee health. However, it remains unclear how specific gut members affect honeybee behaviors. Here, we find that antibiotic exposure disturbs the gut community and influences honeybee phenotypes under field conditions. Using laboratory-generated gnotobiotic bees, we show tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 72 publications
0
50
0
Order By: Relevance
“…Besides, the results of this study showed that lactic acid bacteria were significantly enriched in the midgut of V. v. nigrithorax males. Recent studies show that Lactobacillus Firm-5 species enhances bees' memory and honeybee gut Lactobacillus modulates host learning and memory behaviors via regulating tryptophan metabolism (Li et al, 2021;Zhang et al, 2022). Besides, Bifidobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the results of this study showed that lactic acid bacteria were significantly enriched in the midgut of V. v. nigrithorax males. Recent studies show that Lactobacillus Firm-5 species enhances bees' memory and honeybee gut Lactobacillus modulates host learning and memory behaviors via regulating tryptophan metabolism (Li et al, 2021;Zhang et al, 2022). Besides, Bifidobacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Fisetin could improve hyperuricemia-induced chronic kidney disease via regulating the gut microbiota-mediated Trp metabolism [ 57 ]. Interestingly, honeybee gut lactobacillus modulates host learning and memory behaviors via regulating the Trp metabolism [ 175 ].…”
Section: Potential Application Of Gut Microbiota-derived Trp Metaboli...mentioning
confidence: 99%
“…In the KEGG pathway enrichment analysis (p < 0.05 Figure 2C) between the WT and cKO groups, the biological processes mainly included protein metabolism (protein digestion and absorption), glucose metabolism (glycolysis/gluconeogenesis, carbohydrate digestion, and absorption), and other types of metabolism (methane, tryptophan, and carbon) and hormone regulation (thyroid hormone synthesis). These biological processes directly or indirectly regulate learning and memory (Knezovic et al, 2018;Chaalal et al, 2019;Ajoy et al, 2021;Zhang et al, 2022). Moreover, three downregulated DEGs (Atf4 , t = .…”
Section: Altered Signaling Pathways and Expression Profiles Of Downst...mentioning
confidence: 99%